Bronchopulmonary dysplasia in very preterm infants: Outcome up to preschool age, in a single center of Austria. Issue 4 (17th April 2019) - Reiterer, Friedrich; Scheuchenegger, Anna; Resch, Bernhard; Maurer‐Fellbaum, Ute; Avian, Alexander; Urlesberger, Berndt
Abstract: Background: Bronchopulmonary dysplasia (BPD) is the most frequent chronic lung disease in infancy and is associated with neonatal comorbidity and impairment in pulmonary and neurodevelopmental (ND) long‐term outcome. Methods: This was a retrospective, single‐center, cohort study to compare a cohort of very preterm infants (gestational age [GA], 24 +0 –28 +6 weeks) with BPD ( n = 44), with a cohort of GA‐matched preterm infants without BPD ( n = 44) with regard to neonatal morbidity, incidence of lower respiratory tract infection (LRTI), ND outcome and growth to 2 years' corrected age (CA) and preschool age. Results: Bronchopulmonary dysplasia (incidence, 11.3%) was associated with a higher rate of neonatal pneumonia (26% vs 7%, P = 0.001), longer total duration of mechanical ventilation (mean days, 21 vs 13, P < 0.001), and a higher rate of pulmonary hypertension (20.5% vs 0%, P = 0.002) and of severe retinopathy of prematurity (13.6% vs 0%, P = 0.026). Incidence of LRTI was significantly higher in the BPD infants (50% vs 26%, P = 0.025). ND outcome did not differ between the two groups. Growth at neonatal intensive care unit discharge was similar. In the BPD cohort, rate of weight < 10th percentile was higher at 2 years' CA (52% vs 30%, P = 0.041) and rate of head circumference < 10th percentile was higher at preschool age (59% vs 27%, P = 0.028). Conclusion: Neonatal respiratory morbidity was significantly higher in the BPD cohort, but long‐term ND outcome did not differ. Infants with BPD had poorer growth.